2018
DOI: 10.1111/sms.13316
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of migration background on the development of physical fitness among primary school children

Abstract: Background Children with a low socioeconomic status and migration background are more likely to exhibit unfavorable health behavior patterns and higher BMI scores as well as lower physical activity and physical fitness. Aim To evaluate the effect of migration background on the development of physical fitness among primary school children from first to third grade. Methods In this longitudinal study, height, weight, and physical fitness of primary school children from Tyrol/Austria were measured five times over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Migration background in this study was significantly associated with a lower physical fitness in all three regression models and with a higher proportion of overweight, which is well in accordance with other studies [19,28]. Beside the higher prevalence of overweight, the lower fitness level of adolescents with migration background may be partly caused by an unfavorable and insufficient level of activity in leisure time as results of the MoMo-Study in Germany showed significant effects of a migration background on the level of physical activity in the leisure time of children and adolescents [29].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Migration background in this study was significantly associated with a lower physical fitness in all three regression models and with a higher proportion of overweight, which is well in accordance with other studies [19,28]. Beside the higher prevalence of overweight, the lower fitness level of adolescents with migration background may be partly caused by an unfavorable and insufficient level of activity in leisure time as results of the MoMo-Study in Germany showed significant effects of a migration background on the level of physical activity in the leisure time of children and adolescents [29].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our previous studies on Austrian children and adolescents [16,19,20,21,22] students’ height and weight were measured in sport clothing and barefoot. Body height was measured by using the mobile stadiometer “Seca 217” (Seca, Hamburg, Germany) with an accuracy of 0.1 cm and body weight was measured with the calibrated scale “Grundig PS 2010” (Grundig AG, Neu-Isenburg, Germany) with an accuracy of 0.1 kg.…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations